PERILAKU SISWA TENTANG KESEHATAN GIGI DI SD NEGERI 005 GUNUNG MALELO KOTO KAMPAR HULU TAHUN 2017 - Andalia Roza; - Ervani; Ainil Fitri (LPPM Universitas Muhammadiyah Riau, 2018)
Dental hygiene in children is an important factor that should be considered as early as possible, because tooth decay that occurs at the age of children, can affect the growth of teeth at the next age.The purpose of this research is to know the description of student's behavior about dental health at SD Negeri 005Gunung Malelo Koto Kampar Hulu Year 2017. The population in this study are students of Class IV and V which amounted to 78 people. The sampling technique used in this study is total sampling with a sample size of 78 people. Data collection is done by distributing questionnaires and then processed withediting, coding, data entry, tabulating, cleaning and then analyzed by univariate analysis. The result of the research shows that the students' knowledge about dental health mostly have enough knowledge of 35 people (44,9%), student attitude about dental health majority have positive attitude as much 40 people(51,3%), and student's action about majority dental health ever As many as 52 people (66.7%). It is expected that the State Elementary School 005 Gunung Malelo Koto Kampar Hulu in order to continue the socialization and continuous health education to the students about dental health.